Typification of Cotoneaster koidzumii (Maleae, Rosaceae) and two associated names - Jocou, Adriel Ian (2020)
The typification of the names Cotoneaster koidzumii, Cotoneaster taitoensis, and Cotoneaster formosanus (Rosaceae) is discussed. Lectotypes are designated for C. koidzumii (Herbarium TI), C. taitoensis (TI), and C. formosanus (TAIF; isolectotypes at PE and TI). (Autor de correspondencia: adrieljocou@gmail.com)